Sinkronisasi Qanun Kabupaten Gayo Lues Nomor 9 Tahun 2010 Tentang Pengelolaan dan Pengawasan Hewan Ternak dengan Hukum Adat Masyarakat Gayo Lues - Muhammadin Muhammadin (TANFIDZIY, 2022)
The Gayo Lues District Government issued Qanun number 9 of 2010 concerning the management and supervision of livestock. Based on the observations of the Gayo Lues Regency, which Qanun number 9 of 2010 regarding the management and supervision of livestock was not sufficiently synchronized with the Customary Law of the Gayo Lues people, it is necessary to conduct research into the variables that are causing the implementation of the Qanun to be out of sync. This study is an example of empirical legal research. According to the findings of the first study, the provisions of the Gayo Lues Regency Qanun number 9 of 2010 regarding the management and supervision of livestock mean that Satpol PP will arrest any livestock that roams freely in residential areas, urban areas, public roads, agricultural areas, and plantations. The results of the second research, the provisions of Customary Law, namely Bur cultivation, which is a place for people to farm, and Bur perueren, which is a place for people to herd livestock, were resolved by the traditional leaders of each Gayo Lues community in terms of resolving free-roaming animal problems. Third, impediments such as geographical factors, the lack of personnel in law enforcement, and the place of confinement following an arrest are inadequate.